Knowledge and perceptions of open science among researchers-a case study for Colombia (2018)
Open science can provide researchers diverse opportunities to collaborate, disseminate their research results, generate important impacts in the scientific community, and engage in effective and efficient science for the benefit of society. This study seeks to analyse and evaluate researchers' knowledge of open science in Colombia using a survey to determine adequate instruments with which to improve research in the framework of open science. The aim of the study is to determine researchers' current awareness of open science by considering demographic characteristics to analyse their attitudes, values, and information habits as well as the levels of institutionalism and social appropriation of open science. A representative sample of Colombian researchers was selected from the National Research System. An anonymous online survey consisting of 34 questions was sent to all professors and researchers at Colombian universities and research institutes. Sampling was random and stratified, which allowed for a representative sample of different categories of researchers, and principal component analysis (PCA) was used for the sample design. A total of 1042 responses were received, with a 95% confidence level and a margin of error of 3%. The majority of respondents knew about open science, especially in relation to open science tools (software, repositories, and networks) and open data. Researchers consider open science to be positively impacted by factors such as the rise of digital technologies, the search for new forms of collaboration, the greater availability of open data and information, and public demand for better and more effective science. In contrast, a lack of resources to develop research activities within the open science approach and the limited integration between traditional and open science are identified as the most important barriers to its use in research. These results are important for building adequate open science policy in Colombia. © 2018 by the authors.